Pengaruh Tingkat Perputaran Kas, Tingkat Suku Bunga Kredit Dan Pertumbuhan Kredit Terhadap Profitabilitas Lembaga Perkreditan Desa (LPD) Di Kecamatan Tegallalang, Gianyar - Arta, I Wayan Joni; Kesuma, I Ketut Wijaya (E-Jurnal Manajemen; Vol 3 No 4 (2014), 2014)
Lembaga Perkreditan Desa (LPD) is a non-bank financial institutions that are not regulated by Indonesian Banks regulations, but regulated and authorized by the Bali Provincial Regulation no. 8 of 2002 and LPD management fully assigned to the desa pakraman concerned. The uniqueness of LPDs can be a main attraction for the community, so that with the advantage LPD is expected to compete with other financial institutions in the form of profit through improved performance as measured by profitability ratio. Profitability is measured using one of several ratio of profitability ratio, which uses the calculation of Return On Assets (ROA). To achieve high profitability it is necessary to attention to several factors that affect. This study aims to determine the influential of cash turnover, level of credit interest rates and credit growth to profitability. This research was conducted at Lembaga Perkreditan Desa (LPD) in the Tegallalang District of Gianyar. Secondary data was used in this study is 2009-2012 financial statements. Method of analysis used is the multiple linear regression. The results of analysis of this study is cash turnover and level of credit interest rates have a significant effect on profitability, while the credit growth is not significant influential on profitability. Keywords: Profitability, cash turnover, credit interest rate, credit growth.
Keywords: Profitability, cash turnover, credit interest rate, credit growth.